Experimental Analysis of Graphene/Platinum as Composite Counter Electrode for Dye-Sensitized Solar Cell - Feba Job, Dr. Samuel Mathew2, Reshma Rajendran, Dr. Toby Meyer, Stephanie Narbey (International Journal of Advanced Science and Technology, 2020)
In recent years, there has been a significant increase in the studies on developing effective energy conversion devices which is capable of fulfilling the energy demands without polluting the environment. Among these devices, Dye-Sensitized Solar Cells (DSSCs) have attracted more attention due to their simple fabrication procedure, cost effectiveness, aesthetic features, can be used for indoor light applications, etc. In this research work, we are focusing on the performance of DSSCs by using graphene/platinum as composite counter electrode which is capable of high catalytic activity under indoor as well as outdoor light applications.